2009
DOI: 10.3917/tgs.022.0053
|View full text |Cite
|
Sign up to set email alerts
|

« Petites nièces » et « petites bonnes » à Abidjan

Abstract: Résumé Dans la société abidjanaise contemporaine, la majeure partie du service domestique est effectuée par des fillettes et des jeunes filles âgées de moins de 20 ans. Phénomène ancien, repérable dès les origines de la ville, la mise au travail de « petites bonnes » dans les ménages urbains a connu d’importantes transformations, notamment sous l’influence de la récession économique qui sévit en Côte-d’Ivoire depuis les années 1980. Pour éclairer les logiques contemporaines d’une telle mise à contribution de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 8 publications
(2 reference statements)
0
6
0
2
Order By: Relevance
“…Children might be fostered to wealthier kin or relatives residing in urban areas to redistribute costs of childrearing, especially for schooling which has been a frequently cited reason for sending children to live elsewhere (Akresh 2009;Alber 2003;Archambault and de Laat 2010;Eloundou-Enyegue and Stokes 2002;Goody 1982). Children may also be sent to live with kin or nonrelatives for employment, sometimes as domestic workers or "petites bonnes' or as apprentices (Alber 2018;Bledsoe and Isiugo-Abanihe 1989;Goody 1982;Isaac and Conrad 1982;Isiugo-Abanihe 1985;Jacquemin 2009). Exchanges of children within kinship networks may be part of broader traditions and expectations about kinship or "entrustments," reciprocity, and exchanges of intimacy (Alber 2003;Etienne 1979;Goody 1982Goody , 1970Shipton 2007).…”
Section: An Enduring Institution? Potential Changes In Fostering Over Timementioning
confidence: 99%
“…Children might be fostered to wealthier kin or relatives residing in urban areas to redistribute costs of childrearing, especially for schooling which has been a frequently cited reason for sending children to live elsewhere (Akresh 2009;Alber 2003;Archambault and de Laat 2010;Eloundou-Enyegue and Stokes 2002;Goody 1982). Children may also be sent to live with kin or nonrelatives for employment, sometimes as domestic workers or "petites bonnes' or as apprentices (Alber 2018;Bledsoe and Isiugo-Abanihe 1989;Goody 1982;Isaac and Conrad 1982;Isiugo-Abanihe 1985;Jacquemin 2009). Exchanges of children within kinship networks may be part of broader traditions and expectations about kinship or "entrustments," reciprocity, and exchanges of intimacy (Alber 2003;Etienne 1979;Goody 1982Goody , 1970Shipton 2007).…”
Section: An Enduring Institution? Potential Changes In Fostering Over Timementioning
confidence: 99%
“…The violence suffered and perpetrated, once integrated into the armed forces, are some examples of additional trauma for the individual. Children working in mines (Sastre & Zarama, 1994), in garbage dumps (Camacho, 1986), as domestic servants (Jacquemin, 2009), or sent to the streets as sex workers (Bhukuth & Ballet, 2009;Brial, 2011;Emmanuelli, 2011) are all situations that are undeniably sources of trauma at many levels. These multi-traumatic situations (Mathieu et al, 2012) refer to several factors identified by Bettelheim (1943) to describe an "extreme situation".…”
Section: Figure 1 Effects Of Extreme Development Contexts On Health and Educationmentioning
confidence: 99%
“…Tandis que le caractère urbain du phénomène de la domesticité résidente, et particulièrement dans les capitales (ou les grandes villes), est fortement marqué en Afrique de l'Ouest 29 , cela ne semble pas être le cas pour d'autres capitales, comme Abuja, Khartoum et Nouakchott, qui présentent des pourcentages de domestiques résident•e•s équivalents ou très légèrement supérieurs à ceux évalués à l'échelle nationale, et du reste très faibles (inférieurs à 0,5 % sur l'ensemble de la population résidente), y compris pour le sexe féminin. Abidjan, Dakar, Bamako et Harare présentent des pourcentages de domestiques résident•e•s plus élevés pour le sexe féminin (entre 1,6 et 3 %).…”
Section: Les Sources De Données Démographiques Permettant D'identifie...unclassified